PHILOSOPHICAL METHODS AS FULCRUM OF EDUCATIONAL RESEARCH: A THEORETICAL REVIEW AND ANALYSIS - Amukowa, Wycliffe (British International Journal of Education And Social Sciences, 2021)
As universities continue to be confronted with research productivity there seems to bea micro-political issue regarding the relationship between philosophers of education and educational researchers with educational researchers sidelining philosophers of education. It appears that the zeal for objectivity and reliability hasoften emphasized truth at the expense of relevancy, value, and perhaps most importantly, understanding.Ithas blinded the profession to the fact that research methodologies, like the concepts of knowledge in which they are grounded, are human constructions. These methodologies define particular ways of seeing by designating refined procedures for systematically gathering information and organizing thought. Moreover, insofar as such procedures focus attention on specific aspects of experience to the exclusion of others, research methodologies alsorepresent ways of not seeing.It is in this regard that this paper argues that the demands of the social sciences methodologies have dominated education research thereby putting philosophical methods on the periphery, hence a justification for leveraging.The pressure to have humanities employ the methodology of the social sciences risks chances of academic hegemony.
Keywords: Empirical; Critical; Analytical; Methods; Social Science; Research